INTERFAITH MARRIAGES BASED ON POSITIVE LAW IN INDONESIA AND PRIVATE INTERNATIONAL LAW PRINCIPLES - Benny Krestian Heriawanto (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
This study intends to find out the legitimacy of interfaith marriages according to positive law in Indonesia and private international law, especially marriages held abroad between Indonesian citizens or with a foreign national. The method used in this study was a normative juridical through a legislation approach. Basically, marriages held in Indonesia must follow the provisions of Article 2 jo. Article 56 of Law No. 1 of 1974 concerning marriage. The results of the analysis revealed that interfaith marriages cannot be held either in Indonesia or abroad since they conflict with the principles of private international law and positive law in Indonesia. Tulisan ini disusun untuk mengetahui keabsahan perkawinan beda agama menurut hukum positif Indonesia dan hukum perdata internasional khususnya perkawinan yang dilangsungkan di luar negeri di antara mereka warga negara Indonesia atau dengan seorang warga negara asing. Metode penelitian yang digunakan yaitu yuridis normatif melalui pendekatan perundang undangan, perkawinan yang dilangsungkan di Indonesia harus memenuhi ketentuan Pasal 2 jo. Pasal 56 Undang undang Nomor 1 Tahun 1974 tentang perkawinan. Hasil kajian dan analisis dapat disimpulkan bahwa perkawinan beda agama tidak dapat dilangsungkan baik di dalam maupun di luar negeri karena bertentangan dengan asas asas hukum perdata internasional dan hukum positif Indonesia.